Bird-related Component of Croatian Surnames - Lasić , Josip (Poznańskie Studia Slawistyczne, 2021)
FFindings of the previous research suggest that, although the first records of surnames on the territory of the contemporary Republic of Croatia date back to the 12th century, it is with the Council of Trent (1545–1563) that they became increasingly and extensively used (Frančić, 2015, 229). As far as contemporary surnames are concerned, their structure is regarded to be well established and easily detectable. Their frequency and distribution have also been the topics of much of previous research. Namely, the 2011 census showed that over thirty-three thousand surnames were registered in the Republic of Croatia. For the purposes of this paper, a group of surnames with a bird-related component – ornithonyms – has been singled out from the abovementioned list. The analysed corpus, consisting of approximately three hundred surnames with a component related to bird species, subspecies of groups, is of particular importance since, due to a number of linguistic and non-linguistic obstacles to the creation of a unique “bird” corpus, this interesting group of Croatian surnames has not been sufficiently described by Croatian linguists so far. indings of the previous research suggest that, although the first records of surnames on the territory of the contemporary Republic of Croatia date back to the 12th century, it is with the Council of Trent (1545–1563) that they became increasingly and extensively used (Frančić, 2015, 229). As far as contemporary surnames are concerned, their structure is regarded to be well established and easily detectable. Their frequency and distribution have also been the topics of much of previous research. Namely, the 2011 census showed that over thirty-three thousand surnames were registered in the Republic of Croatia. For the purposes of this paper, a group of surnames with a bird-related component – ornithonyms – has been singled out from the abovementioned list. The analysed corpus, consisting of approximately three hundred surnames with a component related to bird species, subspecies of groups, is of particular importance since, due to a number of linguistic and non-linguistic obstacles to the creation of a unique “bird” corpus, this interesting group of Croatian surnames has not been sufficiently described by Croatian linguists so far.